What she knew ebook A novel. - Macmillan, Gilly (2016)
THE NEW YORK TIMES BESTSELLER In her enthralling debut, Gilly Macmillan explores a mother's search for her missing son, weaving a taut psychological thriller as gripping and skillful as The Girl on the Train and The Guilty One. In a heartbeat, everything changes... Rachel Jenner is walking in a Bristol park with her eight-year-old son, Ben, when he asks if he can run ahead. It's an ordinary request on an ordinary Sunday afternoon, and Rachel has no reason to worry—until Ben vanishes. Police are called, search parties go out, and Rachel, already insecure after her recent divorce, feels herself coming undone. As hours and then days pass without a sign of Ben, everyone who knew him is called into question, from Rachel's newly married ex-husband to her mother-of-the-year sister. Inevitably, media attention focuses on Rachel too, and the public's attitude toward her begins to shift from sympathy to suspicion. As she desperately pieces together the threadbare clues, Rachel realizes that nothing is quite as she imagined it to be, not even her own judgment. And the greatest dangers may lie not in the anonymous strangers of every parent's nightmares, but behind the familiar smiles of those she trusts the most. Where is Ben? The clock is ticking...